Analytical Considerations in Nanoscale Flow Cytometry of Extracellular Vesicles to Achieve Data Linearity - Gomes, Janice; Lucien, Fabrice; Cooper, Tyler T.; Kim, Yohan; Williams, Karla C.; Liao, XinYang; Kaufman, Lauren; Lagugné-Labarthet, Francois; Kenyon, Oliver; Boysen, Justin; Kay, Neil E.; McIntyre, Christopher W.; Leong, Hon S. (Thrombosis and Haemostasis, 2018)
Background Platelet microparticles (PMPs) and their abundance in the blood are a prognostic biomarker in thrombotic disorders and cancer. Nanoscale flow cytometry (nFC) is ideal for high-throughput analysis of PMPs but these clinical assays have not been developed previously.Objective This article demonstrates that nFC is a suitable technology to enumerate PMPs present in plasma samples in a clinical setting.Materials and Methods nFC was performed using the Apogee A50-Micro instrument. Instrument settings and acquisition parameters were developed with the use of fluorescent beads and plasma samples. Sample preparation and handling was also optimized.Results nFC allows for linear detection of particles between approximately 200 and 1,000 nm based on calibration beads and was dependent on dilution factor and flow rate. Linearity in event analysis as samples became more diluted was lost when events approximately 100 nm were gated while linearity was maintained despite dilution of sample in events larger than 200 nm in diameter. Higher flow rates lead to an under-estimation of events analysed per microlitre of analyte and this was more pronounced when plasma samples were not diluted more than 1/20×.Conclusion nFC offers multi-parametric analysis of PMPs when optimal calibration of acquisition and sample processing settings is performed. Analysis of plasmas from metastatic prostate cancer patients and leukaemia patients revealed that PMP levels were larger than 100 nm and were equally abundant in patients that responded to or failed androgen deprivation therapy or between patients representing different stages of leukaemia.
Keywords: cancer; microparticles; flow cytometry